Numerical simulation of tornado turbulent flame - Wee, Arnold Chuan Wen (2017)
This report aims to extract insights on the behavior of a tornado flame at varying boundary conditions. A jet flame is contained in a controlled volume of a cylinder with an inlet of fuel and air from the bottom base and an outlet of air at the top. Methane is the fuel used in this report. Boundary conditions are set for the velocity of the inlet fuel, axial air velocity and tangential air velocity. Simulations are then run and contour results for static pressure, velocities in the x-axis and y-axis and mass fraction of the fuel are recorded, compared and analysed. The results obtained are mostly expected except for some results for velocities in the x-axis and y-axis which are out of scope of this report and hence could be a point of interest for future work.